Chemically Enhanced Immunogenicity of Bacteria by Supramolecular Functionalization with an Adjuvant. (4th November 2022) - Duszenko, Nikolas; van Willigen, Danny M.; Bunschoten, Anton; Velders, Aldrik H.; Roestenberg, Meta; van Leeuwen, Fijs W. B.
Abstract: Many pathogens blunt immune responses because they lack immunogenic structural features, which typically results in disease. Here, we show evidence suggesting that pathogen immunogenicity can be chemically enhanced. Using supramolecular host‐guest chemistry, we complexed onto the surface of a poorly immunogenic bacterium ( Staphylococcus aureus ) a TLR7 agonist‐based adjuvant. "Adjuvanted" bacteria were readily recognized by macrophages and induced a more pro‐inflammatory immunophenotype. Future applications of this concept could yield treatment modalities that bolster the immune system's response to pathogenic microbes. Abstract : Poorly immunogenic pathogens are a major cause of infectious disease. We chemically modified the surface of such a pathogen ( Staphylococcus aureus ) with a synthetic adjuvant to boost immunogenicity. "Adjuvanted" S. aureus induced improved immune responses in macrophages compared to unadulterated bacteria.